SENI HIDUP MINIMALIS SANTRI: STUDI FENOMENOLOGIS DI PONDOK PESANTREN ANNUQAYAH LUBANGSA SELATAN - Try Asih Nur Khodijah (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
This study aims to reveal three things: First, what is the picture of a minimalist lifestyle among students. Second, how is the influence of a minimalist lifestyle on the lives of students, and third, what are the inhibiting and supporting factors in implementing a minimalist lifestyle among students. In order to facilitate this goal, the researcher relies on a phenomenological method with three theories, namely faculty theory to measure the stages of the minimalist attitude of students, Fumio Sasaki's minimalist theory as a detector of student minimalism, and tazkiyatun nafs to examine the Sufistic values contained. This research concludes that the life style of students has minimalist and religious values. They have implemented a simple life with limited facilities. The lifestyle model they apply has a positive impact on their lives in the form of being physically healthy, economically, learning, socially, and applying the rules that have been set. In implementing this, there are several inhibiting factors in the form of high market tension, and supporting factors in the form of parenting patterns, support from friends and the application of discipline, as well as individual awareness.